The Development of Ecotourism Studies in Indonesia: A Bibliometric Analysis of National and International Publications - Bimo Kuncoro Jati; Rachmadina Rafika Triani; Riswano; Mulyati; Christiana Mayang Anggraeni Stj (Politeknik Sahid, 2026)
This study aims to examine the development of ecotourism in Indonesia through a bibliometric approach based on national and international publications. The urgency of this research lies in the pivotal role of ecotourism as a form of sustainable tourism that not only contributes to environmental preservation but also promotes local community empowerment and economic well-being. As global attention toward sustainability increases, ecotourism has emerged as a strategic topic in academic literature. However, a comprehensive and systematic mapping of ecotourism research using reputable scientific databases is still lacking. Therefore, this study focuses on mapping publication trends, identifying key authors, institutions, and countries, as well as exploring dominant themes and keywords in ecotourism literature. This research employs a qualitative approach through Systematic Literature Review (SLR) and bibliometric analysis of ecotourism publications in Indonesia from 2010 to 2025. Data were collected from Scopus, Web of Science, Garuda, and Google Scholar to map publication trends, author collaborations, and dominant themes using co-occurrence keyword analysis. Inclusion criteria were established to ensure article relevance, limited to journal and conference publications within the 2010–2025 period. The results are expected to provide theoretical contributions by offering a comprehensive mapping of ecotourism literature and practical implications in the form of recommendations for academics, researchers, and policymakers to direct ecotourism studies toward more strategic and relevant areas. Consequently, this research not only highlights Indonesia’s position within the global literature landscape but also opens opportunities for collaboration and strengthens future ecotourism research